An investigation into the english translational versions of pham duy’s songs in terms of semantic and syntactic features - Huỳnh Thị Thu Hà (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Nowadays, music is an interesting topic for all people not only in Vietnam but also in the world. Music brings happiness, vitality, belief, optimism, joy of living to each listener. In fact, with the integration of western life and culture, music has recently become an essential part of global cultural communication. This is the reason why people incline toward singing and listening Vietnamese music together with English lyrics and vice versa. Therefore, the need for song translation boots quickly. The primary aim of the present study is to gain an understanding of the translation process involved when translating song lyrics by investigating syntactic and semantic translation features that occur in 14 Pham Duy‟s songs from Vietnamese into English. Comparing the source texts to the translated texts, descriptive and contrastive methods are chosen as the main ones. Besides, quantitative and qualitative analysis are also used to support the study. Taking into account of syntactic: Structure-shifts, Class-shifts,